Intramolecular Diels–Alder Reactions of Cycloalkenones: Translation of High endo Selectivity to trans Junctions - Ross, Audrey G. (2012)
Intramolecular Diels–Alder (IMDA) reactions of cyclobutenone and larger cycloalkenones are described. High levels of endo addition attained from Lewis acid catalysis translate to trans hydrindene junctions upon fragmentation of the tricyclic adducts.